The use of children in cocoa production in sekyere south district in ashanti region, ghana: is this child labour or an apprenticeship training? - PKB Asamoah (International Journal of Agricultural Research, Innovation and Technology, 2018)
Concerns have been growing in Ghana about the employment of children, aged between 5-17 years, in cocoa production activities. This concern is echoed by the International Labour Organisation in its attempt to eliminate Worst Form of Child Labour. The objectives of the study were as to: investigate whether the labour of the children are paid for; determine the extent of children’s involvement; and investigate the risks they are exposed to. Using Focus Group Discussions (FGDs), participant groups made up of women, men, children and opinion leaders were purposely selected from 10 cocoa producing communities from the study area. Structured questionnaires were also administered to 50 cocoa farmers through face-to-face interviews. The study revealed that harvesting is the stage in the cocoa production process that children are directly and actively involved. The study concludes by indicating that child labour and cocoa production are inseparable in the cocoa producing areas in the study site.